TRANSFORMASI STRATEGIS SATUAN PENDIDIKAN MENUJU SMART SCHOOL: ANALISIS FORMULASI DAN IMPLEMENTASI RENSTRA 2026–2030 DI SMA NEGERI 1 SANGASANGA - Irmawati; Winaryati; Arie Ekayudhistira Kirana Tejawati; Friska Umi Puspitasari; Ramadiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The decline in literacy competence and the challenges of technological disruption require secondary education units to reform conventional governance into data-driven planning. This study aims to analyze the formulation and roadmap of the Strategic Plan (RENSTRA) of SMA Negeri 1 Sangasanga for the 2026–2030 period, focusing on digital transformation and pedagogical innovation. Using a descriptive qualitative method with a case study approach, this study audited institutional capacity based on the Education Report Card instrument, then quantified it using IFAS and EFAS matrix analysis. The results showed that the school obtained an IFAS score of 2.90 and an EFAS score of 3.10, positioning the institution in Quadrant I (Growth Strategy). This strategy is operationalized into a phased five-year medium-term roadmap, starting with a digitalization foundation (E-Library) to mitigate literacy degradation, followed by character strengthening, research classes, global competitiveness, and the realization of a Smart School ecosystem by 2030. The sustainability of this roadmap is locked using the Balanced Scorecard framework and collaborative governance principles through funding diversification (government, committee, alumni, and PT ABN's CSR) and partnerships with higher education (Universitas Mulawarman). This study concludes that the synchronization of data-driven planning, digital ecosystem integration, and partnership resilience are the critical success factors for transforming school quality without abandoning the roots of local wisdom.